Understanding the impact of climate change and resilience among highlanders in northern parts of Bhutan: A case study in Gasa district - Dorji, Tshering; Yangzom, Deki; Norbu, Nima; Rinchen, Sangay; Dorjee, Jambay; Tenzin, Tenzin (PLOS climate, 2023)
Mountainous regions are affected the most by climate change across the world. The livelihood of highlanders primarily depends on livestock farming and natural resources. In Bhutan, yak farming and sale of Cordyceps sinensis (caterpillar fungus)remain the main source of income for most highlanders. We conducted a study to understand the impact of climate change on the community livelihoods in Bhutan. A cross-sectional survey was conducted and interviewed 132 household heads, two focus group discussions of 20 respondents (10 in each group), and key informant interviews (n = 5) in two highland communities (i.e., Laya and Lunana) of Gasa district in northern Bhutan between August 2019 and February 2020. The study revealed that the caterpillar fungus (78.8%) is the major source of income for highland communities which overtook the yak farming practices since its legalization in 2004. More than 80% of households have abandoned yak farming due to its poor economic return because of the decreased utility of yak for meat purposes and other socio-cultural related practices. The majority of the respondents (91%) expressed concern that climate change is posing a threat to the growth and subsequent harvest of caterpillar fungus. The highland people reported emergence of insects/vectors in their community and mosquitoes were the most frequently reported (85%) insect. A small proportion of respondents (1.5%) were concerned about the grazing habitat of the yaks due to the change in the botanical composition of the rangeland. Given that there is a decrease in caterpillar fungus, which is the main source of income for highland communities, this study calls for a climate-resilient community-based economic opportunity for the sustainable livelihood of highland communities. Furthermore, we recommend a detailed study of the negative impacts due to climate change on freshwater resources, the distribution of vectors and vector-borne diseases, and rangeland ecology in the highland.